O multidisciplinarnosti timskega dela na centrih za socialno delo - Rape Žiberna, Tamara (Socialno delo, 2023)
The research question, is team work at centres for social work multidisciplinary, is answered on the basis of the studied domestic and foreign literature, as well as qualitative and quantitative data obtained through interviews with social workers from social work centres (n = 21) and a survey among employees of social work centres in Slovenia (n = 197). The results show an increasing use of the term ‚multidisciplinary team work‘, which is also used and misused in various laws and regulations, although this term is very rarely defined. The paper also contains a proposal for the clearer definition of team work in social work and, based on a comparison with foreign countries, the author suggests more appropriate terms in the Slovene language for describing certain types of team work.
Keywords: centri za socialno delo; interdisciplinary team work; meddisciplinarno timsko delo; medinstitucionalno timsko delo; mešane metode; mixed methods; social work; socialno delo; transdisciplinary team work